Forming Religious Psychological Immunity In Young People - Principle Of Peace And Stability - Kasimova Zebo Khamidovna (Genius Journals, 2025)
This article deals with the formation of religious-psychological immunity as a principle of peace and stability, which is a fundamental principle of world religions. In the conditions of global challenges faced by mankind, this principle acquires special significance. Also in the article the factors of formation of religious-psychological immunity and practical measures to strengthen religious-psychological immunity are given.
Keywords: psychological immunity; formation; strengthening